2014
DOI: 10.1371/journal.pone.0103229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Tanshinone IIA on Rat Hepatic Stellate Cells

Abstract: BackgroundAnti-inflammation via inhibition of NF-κB pathways in hepatic stellate cells (HSCs) is one therapeutic approach to hepatic fibrosis. Tanshinone IIA (C19H18O3, Tan IIA) is a lipophilic diterpene isolated from Salvia miltiorrhiza Bunge, with reported anti-inflammatory activity. We tested whether Tan IIA could inhibit HSC activation.Materials and MethodsThe cell line of rat hepatic stellate cells (HSC-T6) was stimulated with lipopolysaccharide (LPS) (100 ng/ml). Cytotoxicity was assessed by MTT assay. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Moreover, tanshinone IIA attenuated LPS-induced mRNA expressions of CCL2, CCL3, CCL5, IL-1β, TNF-α, IL-6, ICAM-1, iNOS and α-SMA in HSC-T6 cells. The present results demonstrated that tanshinone IIA decreased LPS-induced HSC activation [33] .…”
Section: Inhibitory Effect Of Tanshinone Iia On Rat Hepatic Satellitesupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, tanshinone IIA attenuated LPS-induced mRNA expressions of CCL2, CCL3, CCL5, IL-1β, TNF-α, IL-6, ICAM-1, iNOS and α-SMA in HSC-T6 cells. The present results demonstrated that tanshinone IIA decreased LPS-induced HSC activation [33] .…”
Section: Inhibitory Effect Of Tanshinone Iia On Rat Hepatic Satellitesupporting
confidence: 67%
“…and his colleagues determined whether tanshinone IIA protects neurons against Aβ (25-35)-induced cytotoxicity and detected the association of this protective effect with calpain and the p35/Cdk5 pathway. The results showed that tanshinone IIA protected neurons against the neurotoxicity of Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), increased the viability of neurons, decreased expression of phosphorylated tau in neurons induced by Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), improved the impairment of the cell ultra-structure (such as nuclear condensation and fragmentation, and neurofibril collapse). Further more, the authors found that tanshinone IIA possessed neuroprotective action and the protection may involve in calpain and the p35/Cdk5 pathway.…”
Section: A N T I -I N F L a M M A T O R Y E F F E C T S O F Tanshinonmentioning
confidence: 99%
“…These results indicated that inhibition of JNK in the spinal dorsal horn of SNL rats was consistent with the analgesic effect of TIIAS. Recent studies have indicated that in some pathological processes, activation of JNK can be inhibited by TIIAS, especially in the signal transduction of anti-inflammatory and anti-apoptotic pathways [ 39 - 42 ]. The pro-inflammatory cytokines, especially TNF-α and IL-1β, induced by peripheral nerve injury, are essential triggers for the activation of JNK in spinal astrocytes underlying the development of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…NF-jB activation in neurons is mediated primarily by the binding of p50 and p65 to the jB DNA recognition sequence. Interleukin-1b (IL-1b) and proinflammatory cytokines tumor necrosis factor-a (TNF-a) are known as stimuli that more strongly activate neuronal NFjB, than other agents like L-glutamate [14,15]. Therefore, inhibitors of the NF-jB pathway may become important alternatives in preventing further anti-neuroinflammation in the microglial over-activation.…”
Section: Introductionmentioning
confidence: 99%